Causal Factors of Acceptance Smart Home Technology System Among Adolescents in Zhengzhou, Henan - Yilin Zhang; Somchai Seviset; Thanate Piromgarn (Revista de Gestão Social e Ambiental, 2024)
Objective: This study aims to investigate the factors influencing the behavioral habits of adolescent users regarding the use of smart home products. Theoretical Framework: Smart homes represent an innovative integration of electronic devices within a private home environment, utilizing technologies such as the Internet of Things, automatic control, and network communications to enhance efficiency, energy conservation, and security. This study is grounded in the theoretical framework of technology acceptance models and behavioral intentions to understand the adoption of smart home technology systems among adolescents. Method: Qualitative research was conducted using a structured questionnaire to collect data from 390 users in Zhengzhou, Henan. The data were filtered to eliminate outliers. Descriptive statistics, confirmatory factor analysis, and structural equation modeling were employed to determine the style and scale of smart home product design and the relationship between user attitudes and usage behavior. Results and Conclusion: The study found a direct and positive relationship between smart home product attitudes and teenage users' behavioral intentions. Additionally, it revealed that user personal capabilities significantly predict the actual adoption of smart home technology systems among adolescents. The findings provide valuable insights for designing smart home technology systems and products tailored to adolescent users in Zhengzhou, Henan, contributing to the advancement of management practices in the field of smart home technology. Originality/Value: This study contributes to the advancement of science in the field of smart home technology by revealing causal factors influencing the acceptance of smart home technology systems among adolescents in Zhengzhou, Henan.
Keywords: Technology Adoption and User Behaviour; Consumer Retail Behavior Studies